Gene Expression Profiling in Cancer - Vlachakis, Dimitrios (IntechOpen, 2019)
The contribution of modern-day genetics in designing efficient gene expression profiles for cancer is immense. The progress of technology and science in recent years provides the opportunity for discovery and application of new techniques for treating various diseases that affect humanity. Methods for finding and analyzing the profile of gene expression of infected cells give scientists the ability to develop more targeted and effective treatments, especially for diseases such as cancer. The development of gene expression profiling is one of the most important achievements in cancer genetics in our time. It is essentially the driving force behind personalized and precision medicine. This book highlights recent developments, applications, and breakthroughs in the field of gene expression profiling in cancer.